Social praxis, party, and class relations today. - Malo, Egni (Academicus, 2014)
Today's political sociologists are once again interested in the study of the crisis of mass-based parties, anti-politics and anti-parliamentarism, crisis in the authority of the political class, prevailing corporate interests within republican institutions, and populism. Political sociology however, takes the party, as a construct of political sociology alone, without consideration upon its militancy and action, as the party, which objectifies the foundation of a State, and as a result the party becomes, simply an historical category.1 We approach the problem of the modern state from many angles; analysing the nature of a political party as such; the ideological dangers of determinism and spontaneism which a party necessarily must struggle with; the type of non-administrative internal regime which is necessary for a party to be effective and so on.2 The problem we seek to elaborate is the specific character of the collective action that makes possible the passage from a sectored, corporate and subordinate role of purely negative opposition, to a leading role of conscious action towards not merely a partial adjustment within the system, but posing the issue of the State in its entirety. In developing this theme - as a study of the real relations between the political party, the classes and the State - a two-fold consideration is devoted to the study of Machiavelli and Marx: first from the angle of the real relations between the two, as thinkers of revolutionary politics, of action; and secondly from a perspective which would derive from the Marxist doctrines an articulated system of contemporary politics, as found in The Prince.